Meat Matters : Ethnographic Refractions of the Beta Israel - Salamon, Hagar (Book collections on Project MUSE., 2023)
"Meat Matters offers a portrait of the lives of Ethiopian Jews as it is reflected and refracted thought the symbolism of meat. Drawing upon thirty years of fieldwork, this beautifully written and innovatively constructed ethnography tells the story of the Beta Israel, who began immigrating from Ethiopia to Israel in the 1970s. Once in Israel, their world changed in formerly unimaginable ways, such as conversion under Rabbinic restrictions, moving into multistory buildings, different attitudes toward gender and reproduction, and perhaps above all, the newly acquired distinctiveness of the color of their bodies. In the face of such changes, the Beta Israel held on to a key idiom in their lives: meat. The community continues to be organized into kirchas, groups of friends and family who purchase and raise cows, then butcher and divide the animal's body into small and equal chunks, which are distributed among the kircha through a lottery ritual. Flowing back and forth between Ethiopia to Israel, Meat Matters follows the many strands of significance surrounding cows and meat, ultimately forming a vibrant web of meaning at the heart of the Beta Israel community today"--